Carotenoids Do Not Protect Bacteriochlorophylls in Isolated Light-Harvesting LH2 Complexes of Photosynthetic Bacteria from Destructive Interactions with Singlet Oxygen - Zoya K. Makhneva; Maksim A. Bolshakov; Andrey A. Moskalenko (Molecules, 2021)
The effect of singlet oxygen on light-harvesting (LH) complexes has been studied for a number of sulfur (S+) and nonsulfur (S−) photosynthetic bacteria. The visible/near-IR absorption spectra of the standard LH2 complexes (B800-850) of Allochromatium (Alc.) vinosum (S+), Rhodobacter (Rba.) sphaeroides (S−), Rhodoblastus (Rbl.) acidophilus (S−), and Rhodopseudomonas (Rps.) palustris (S−), two types LH2/LH3 (B800-850 and B800-830) of Thiorhodospira (T.) sibirica (S+), and an unusual LH2 complex (B800-827) of Marichromatium (Mch.) purpuratum (S+) or the LH1 complex from Rhodospirillum (Rsp.) rubrum (S−) were measured in aqueous buffer suspensions in the presence of singlet oxygen generated by the illumination of the dye Rose Bengal (RB). The content of carotenoids in the samples was determined using HPLC analysis. The LH2 complex of Alc. vinosum and T. sibirica with a reduced content of carotenoids was obtained from cells grown in the presence of diphenylamine (DPA), and LH complexes were obtained from the carotenoidless mutant of Rba. sphaeroides R26.1 and Rps. rubrum G9. We found that LH2 complexes containing a complete set of carotenoids were quite resistant to the destructive action of singlet oxygen in the case of Rba. sphaeroides and Mch. purpuratum. Complexes of other bacteria were much less stable, which can be judged by a strong irreversible decrease in the bacteriochlorophyll (BChl) absorption bands (at 850 or 830 nm, respectively) for sulfur bacteria and absorption bands (at 850 and 800 nm) for nonsulfur bacteria. Simultaneously, we observe the appearance of the oxidized product 3-acetyl-chlorophyll (AcChl) absorbing near 700 nm. Moreover, a decrease in the amount of carotenoids enhanced the spectral stability to the action of singlet oxygen of the LH2 and LH3 complexes from sulfur bacteria and kept it at the same level as in the control samples for carotenoidless mutants of nonsulfur bacteria. These results are discussed in terms of the current hypothesis on the protective functions of carotenoids in bacterial photosynthesis. We suggest that the ability of carotenoids to quench singlet oxygen (well-established in vitro) is not well realized in photosynthetic bacteria. We compared the oxidation of BChl850 in LH2 complexes of sulfur bacteria under the action of singlet oxygen (in the presence of 50 μM RB) or blue light absorbed by carotenoids. These processes are very similar: {[BChl + (RB or carotenoid) + light] + O2} → AcChl. We speculate that carotenoids are capable of generating singlet oxygen when illuminated. The mechanism of this process is not yet clear.